Constraint programming approach for multi-objective two-sided assembly line balancing problem with multi-operator stations. Issue 8 (3rd August 2021) - Kizilay, Damla; Çil, Zeynel Abidin
Abstract : In recent years, the two-sided assembly line (TAL) has become popular since it offers several advantages, such as fewer workstations and movement of fewer workers inside the line. TAL assumes that each mated workstation contains two workstations in parallel, and it can process tasks on the left, on the right or on either side. However, in a traditional TAL, only one worker is responsible for completing the task at each workstation. Dealing with large-size products and massive operations may require more than one operator to perform tasks. This study proposes mixed-integer linear programming and constraint programming (CP) models for the two-sided assembly line balancing problem with multi-operator stations for the purpose of solving small- and large-size problems. Computational results indicate that the CP model finds optimal solutions for all instances. It is useful to highlight that the CP model is highly concise and solved by a black-box, commercial solver.